ANALISIS PERTUMBUHAN PERUSAHAAN, KUALITAS AUDITDAN KONDISI KEUANGAN TERHADAP OPINI AUDIT GOING CONCERN - Adi Prama Cunanjar; Ni Putu Eka Widiastuti, - (FE, UPN "Veteran" Jakarta, 2013)
This research is to test corporate growth variable influence, Quality Audits and Financial Condition for Opinion To Audit Going-concern on enrolled manufacturing business at Indonesian Stock Exchange (BEI) up to period 2006 - 2011. Acquired data of write-up corporate finance which at publication. Total samples are 16 firms by use of method purposive sampling. Population in observational total 96 firms. Logistic regression utilizes t statistic with level trusty 5%. Result observationaling to point out that Financial Condition influentialing to pretty much Opinion application Audits Going-concern Meanwhile other variable in observational it, which is firm growth and quality Audit not ascendant to pretty much Opinion application Audits Going-concern.